2020
DOI: 10.1097/ta.0000000000002668
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation and management of blunt cerebrovascular injury: A practice management guideline from the Eastern Association for the Surgery of Trauma

Abstract: BACKGROUND Blunt cerebrovascular injuries (BCVIs) are associated with significant morbidity and mortality. This guideline evaluates several aspects of BCVI diagnosis and management including the role of screening protocols, criteria for screening cervical spine injuries, and the use of antithrombotic therapy (ATT) and endovascular stents. METHODS Using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology, a taskforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 92 publications
2
78
0
4
Order By: Relevance
“…26 28 The Eastern Association for the Surgery of Trauma in 2020 summarized results from 10 studies on the role of antithrombotics compared with no antithrombotics, favoring antithrombotics for stroke prevention with an OR of 0.20 (95% CI 0.06 to 0.65). 26 Our review clearly agrees with this finding, although we chose not to perform a metaanalysis due to the high risk of bias and heterogeneity of study patients. We found that not treating asymptomatic BCVI had a stroke rate as high as 25%, compared with almost any other treatment modality where the stroke rate was <10%.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…26 28 The Eastern Association for the Surgery of Trauma in 2020 summarized results from 10 studies on the role of antithrombotics compared with no antithrombotics, favoring antithrombotics for stroke prevention with an OR of 0.20 (95% CI 0.06 to 0.65). 26 Our review clearly agrees with this finding, although we chose not to perform a metaanalysis due to the high risk of bias and heterogeneity of study patients. We found that not treating asymptomatic BCVI had a stroke rate as high as 25%, compared with almost any other treatment modality where the stroke rate was <10%.…”
Section: Discussionsupporting
confidence: 74%
“…Major trauma society guidelines recommend antithrombotic therapy, but evidence regarding specific agents, dose, and duration has not been established. 25 26 Clear indications for more invasive therapies, such as endovascular repair or surgery, are also not well established.…”
Section: Introductionmentioning
confidence: 99%
“…TCCF should be considered, and patients with severe head and facial trauma must undergo imaging during the initial evaluation. In our trauma center, computed tomography angiography is performed based on the Denver criteria [ 11 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade extracranial ICA blunt injury should be treated with early systemic anticoagulation or antiplatelet therapy [6,[48][49][50][51]. The Eastern Association for the Surgery of Trauma recommends against the routine use of endovascular stents as an adjunct to antithrombotic therapy in patients with asymptomatic grade II or stable III extracranial ICA blunt injuries [52,53].…”
Section: Evt Prospectmentioning
confidence: 99%